Psychoanalytic thinking on the unhoused mind - Brown, Gabrielle (Routledge, 2019)
Psychoanalytic Thinking on the Unhoused Mind illuminates the psychological underpinnings of current societal problems: homelessness, mental distress, loneliness and states of societal breakdown and exclusion. Illustrated with a broad range of clinical work as well as thoughts on art and literature, the book brings to life complex tensions between the individual psyche, the group, and wider political and cultural structures. 'Unhoused' states of mind are explored in rough sleepers, ex-prisoners, survivors of institutional abuse and family trauma, and people living with personality disorder, addiction, psychosis and dementia. Chapters describe outreach, assessment and long-term psychotherapy, as well as reflective practice with staff teams and care systems, and learning from consultation, supervision and policy development. New therapeutic responses to chronic risk and to resilience are developed from psychoanalytic understandings of difficulties with containment and care. The collection will be of value to psychotherapists and other mental health practitioners, as well as those working in therapeutic, residential and criminal justice settings and outreach services